Serum TNF-α and biomarkers Levels after Tenofovir in Patients with serum HBeAg-Positive Chronic Hepatitis B : Serum TNF-α and biomarkers and Chronic Hepatitis B - Lai, Xijie (Journal of Medical Biochemistry, 2025)
0